2021
DOI: 10.3390/ijerph18126410
|View full text |Cite
|
Sign up to set email alerts
|

Chronological Age, Somatic Maturation and Anthropometric Measures: Association with Physical Performance of Young Male Judo Athletes

Abstract: Sport for children and adolescents must consider growth and maturation to ensure suitable training and competition, and anthropometric variables could be used as bio-banding strategies in youth sport. This investigation aimed to analyze the association between chronological age, biologic maturation, and anthropometric characteristics to explain physical performance of young judo athletes. Sixty-seven judokas (11.0–14.7 years) were assessed for anthropometric and physical performance. Predicted adult stature wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(42 reference statements)
1
6
0
2
Order By: Relevance
“…Similarly, a study conducted by Courel-Ibanez et al [ 39 ] detected a higher number of throws in the SJFT in U15 male amateur judo athletes compared to U13 athletes, showing better performance in older boys, especially when utilizing anaerobic pathways. Giudicelli et al [ 12 ] also found that older male judokas (aged 11.0–14.7 years) performed better in most of the physical tests; however, in their study, the maturation attenuated the age effect in most variables and significantly affected upper body strength.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similarly, a study conducted by Courel-Ibanez et al [ 39 ] detected a higher number of throws in the SJFT in U15 male amateur judo athletes compared to U13 athletes, showing better performance in older boys, especially when utilizing anaerobic pathways. Giudicelli et al [ 12 ] also found that older male judokas (aged 11.0–14.7 years) performed better in most of the physical tests; however, in their study, the maturation attenuated the age effect in most variables and significantly affected upper body strength.…”
Section: Discussionmentioning
confidence: 77%
“…The current literature contains several studies on the effects of somatic maturity and growth on physical performance in young male athletes from team sports [ 4 , 5 , 6 , 7 ]. Most recently, studies have investigated the role of growth and maturity status on physical performance in young male judo athletes [ 8 , 9 , 10 , 11 , 12 ]. Years of formal judo training, growth, and somatic maturity can predict physical performance, when generalized upper and lower limb strength assessments (e.g., medicine ball throw test, handgrip strength, and jump tests) [ 8 , 10 ] and judo-specific tests (e.g., Special Judo Fitness Test and Judogi Grip Strength Test) [ 8 ] are considered.…”
Section: Introductionmentioning
confidence: 99%
“…The age and training experience of the participants were used as the main criteria for dividing into groups. This approach is one of the main ones in sports science [27,29,30]. In the article [29], the division of martial arts athletes was carried out according to these criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the maturation effect on growth and physical performance in young judokas has been highlighted as it seems more relevant than the age effect [ 55 , 56 ]. Additionally, it has been shown that maturation attenuated the age effect and significantly affected upper body and handgrip strength in youth judokas [ 57 ]. This phenomenon could explain why we have so many youth judo athletes competing in higher age categories and being successful in them.…”
Section: Discussionmentioning
confidence: 99%